2010
DOI: 10.3113/fai.2010.0291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Distal Chevron Osteotomy With and Without Lateral Soft Tissue Release for the Treatment of Hallux Valgus

Abstract: Lateral soft tissue release may not be needed for mild or moderate hallux valgus deformities which may prevent decreased range of motion of the first metatarsophalangeal joint, neuritis of dorsal or plantar lateral digital nerve and cosmetic dissatisfaction of a dorsal scar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…Our data also are similar to those associated with other osteotomies currently used for surgical correction of an HV deformity [3,17,19,21].…”
Section: Discussionsupporting
confidence: 75%
“…Our data also are similar to those associated with other osteotomies currently used for surgical correction of an HV deformity [3,17,19,21].…”
Section: Discussionsupporting
confidence: 75%
“…The AOFAS score of 96.3, with improvement of 50 (or 102%) found in our study is at the higher end of the range reported in the literature [22,23]. The radiographic and cosmetic outcome was satisfactory, showing that this is an acceptable technique for young athletes.…”
Section: Discussionsupporting
confidence: 74%
“…They reported that soft tissue release should be contraindicated in cases of preoperative MTPJ limitation, despite the greater angular correction provided by the lateral soft tissue release. Lee et al (43) also reported a high rate of dorsal and plantar digital neuritis in patients undergoing soft tissue release, and this risk increased in cases performed percutaneously (45). Finally, as an open procedure, lateral soft tissue release requires a second incision, which is cosmetically undesirable.…”
Section: Discussionmentioning
confidence: 95%
“…Lee et al (43) and Granberry and Hickey (44) associated soft tissue release with greater postoperative stiffness of the MTPJ (25). They reported that soft tissue release should be contraindicated in cases of preoperative MTPJ limitation, despite the greater angular correction provided by the lateral soft tissue release.…”
Section: Discussionmentioning
confidence: 96%